The Relationship Between Problem-Solving Ability with Academic Procrastinating and Academic Self-Efficacy Among Male First Grade High School Students - Bahreini, Tabassom (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the relationship between problem-solving skill with academic procrastination and self-efficacy among male first grade high school students. This research method was descriptive and correlational. The participants consisted of all male first grade high school students from Tehran's 4th District in the academic year 1396. A number of 250 students were selected through multistage cluster sampling. The instruments of this study were academic self-efficacy questionnaire (Jinks & Morgan, 1999), problem-solving inventory (Heppner & Peterson, 1982), and academic procrastination questionnaire (Solomon & Ruthblum, 1984). Data were analyzed by descriptive statics, coefficient correlation, and regression using IBM SPSS-22 software. The results showed a position and significant (P